2018
DOI: 10.1021/acsnano.8b02376
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Gold Nanoparticles for Nanostructure Imaging Mass Spectrometry

Abstract: Nanostructure imaging mass spectrometry (NIMS) with fluorinated gold nanoparticles (f-AuNPs) is a nanoparticle assisted laser desorption/ionization approach that requires low laser energy and has demonstrated high sensitivity. Here we describe NIMS with f-AuNPs for the comprehensive analysis of metabolites in biological tissues. F-AuNPs assist in desorption/ionization by laser-induced release of the fluorocarbon chains with minimal background noise. Since the energy barrier required to release the fluorocarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 77 publications
(129 reference statements)
1
44
0
Order By: Relevance
“…We summed the ion currents of these two species and compared the four types of AuNP ligands. As shown in Figure 3A, the signal intensity for linoleic acid from AuNP[D‐1‐H] (= 1‐decanethiol) was significantly higher than those obtained for the other three ligands, which is consistent with previous findings, showing that signal intensities from hydrophobic nanomaterials are higher than from hydrophilic nanomaterials 28 . This is related to higher local temperatures obtained with the hydrophobic nanomaterials and thus slower energy dispersion.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We summed the ion currents of these two species and compared the four types of AuNP ligands. As shown in Figure 3A, the signal intensity for linoleic acid from AuNP[D‐1‐H] (= 1‐decanethiol) was significantly higher than those obtained for the other three ligands, which is consistent with previous findings, showing that signal intensities from hydrophobic nanomaterials are higher than from hydrophilic nanomaterials 28 . This is related to higher local temperatures obtained with the hydrophobic nanomaterials and thus slower energy dispersion.…”
Section: Resultssupporting
confidence: 89%
“…Using gold nanorods (AuNR), Castellana et al demonstrated that infrared laser desorption/ionization-MS was capable of analyzing peptides very efficiently. 27 Furthermore, fluorinated AuNP were prepared for comprehensive analysis of metabolites in biological tissues using nanostructure imaging mass spectrometry (NIMS) with minimal background noise levels and high sensitivity as illustrated by Palermo et al 28 Only low laser energies were required during this process, which lead to very gentle desorption/ionization conditions with limited in-source fragmentation of the metabolites. Chiang et al 29 used mixed gold nanoparticles with diameters of 3 and 14 nm as probes for SALDI-MS to detect amino-thiol groups.…”
mentioning
confidence: 99%
“…This fluorinated Au NP was further utilized for the comprehensive imaging of metabolites from the colon of mice exposed to three different diets by the same group. [158] Vachet et al developed a dual-mode MS imaging method to evaluate the stability of monolayer-functionalized Au NPs in vivo. [159] By using laser ablation inductively coupled plasma MS to monitor Au core and LDI-MS to monitor surface ligands, this approach revealed the site-specifically NP stability at the organ and suborgan level.…”
Section: Ms Imagingmentioning
confidence: 99%
“…Polyvinylpyrrolidone-capped AgNPs have been utilized for analysis of brain [69], and AuNPs with alkylamine surface modifications have been used for imaging of glycosphingolipids in the brain [70]. Fluorinated AuNPs have been shown to detect carbohydrates, lipids, bile acids, sulfur metabolites, amino acids, nucleotide precursors, and more in mouse colon [71].…”
Section: Alternative Matrix Materialsmentioning
confidence: 99%